The genesis of grammar : a reconstruction - Heine, Bernd, 1939- (Studies in the evolution of language, 2007)
This book reconstructs what the earliest grammars might have been and shows how they could have led to the languages of modern humankind. It considers whether these languages derive from a single ancestral language; what the structure of language was when it first evolved; and how the properties associated with modern human languages first arose. - ;"This book reconstructs what the earliest grammars might have been and shows how they could have led to the languages of modern humankind. "Like other biological phenomena, language cannot be fully understood without reference to its evol.